Design analysis and experimental validation of a multi‐level inverter for vehicle to home application - Mohd Khalid (681127) (2023)
Robust and economic inverting devices are needed with the increasing practice of direct current (DC) sources. This paper proposes a compact multi‐level inverter topology for Vehicle to Home (V2H) application under different load conditions. A reduced number of switches with a single DC source (EV battery) is used to generate the 11‐level of output voltage and current waveform. The proposed topology is quite simple in structure and ensures the increase of two levels with each additional switch. The complete power loss analysis is performed for the proposed inverter. The MATLAB/Simulink is used to perform the simulation, and the results are validated through the experimental hardware setup designed. The comparison with the existing multi‐level inverter (MLI) topologies and literature shows the significant acceptability and reliability of the proposed multi‐level inverter. The operation of the proposed MLI under various loading conditions has expressed robustness for V2H application. The simulated and experimental data confirm that both results have a good agreement in terms of THD and output power. The output voltage levels of the proposed inverter could be flexibly varied by employing different numbers of switching capacitors. Other Information Published in: IET Renewable Power Generation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/rpg2.12620